How to Save Jobs and Build Back Better: Employee Ownership Transitions as a Key to an Equitable Economic Recovery - Brown, Rob (Maine Policy Review, 2021)
Prior to the COVID-19 pandemic, Maine was already on the leading edge of what was termed the “silver tsunami,” the looming retirement of aging business owners with no real plan for how to exit their businesses. While half of business owners nationally are over age 50, in rural regions such as Maine, nearly half are over 60. Fewer than one in five business owners have a documented exit plan, and most don’t understand the process or options. Rob Brown examines the effect of the COVID-19 pandemic on this issue and argues that helping businesses transition to employee ownership will be good for workers, owners, and Maine’s economy in general.